Critical evaluation of biochar effects on methane production and process stability in anaerobic digestion - Hu, Jiahui; Stenchly, Kathrin; Gwenzi, Willis; Wachendorf, Michael; Kaetzl, Korbinian (Frontiers in Energy Research, 2023)
Biochar is an emerging biomaterial for managing residual biomass while simultaneously sequestering carbon. To extend the biochar value chain, applying biochar to enhance anaerobic digestion (AD) processes is gaining attention in the context of a circular economy and cascading use of biomass. However, the comparative effects of various biochar dosages under normal and severe AD conditions are still unclear. To further our understanding of its potential application, this work investigated the impact of adding various biochar dosages on AD processes under normal and high substrate loadings. Three inoculum-to-substrate ratios (ISRs): one representing normal substrate loading (ISR 2) and two representing substrate overloading (ISR 1 and 0.5) were investigated. Each substrate loading rate was tested with a biochar dosage of 0% (control), 10%, and 25% based on substrate volatile solids. The results revealed that under the severe condition of high substrate overload (ISR 0.5), a high biochar dosage of 25% significantly increased cumulative methane production by 5.6% (p = 0.06) when compared to the control. Under the same condition (ISR 0.5, 25%), the time required to achieve a particular extent of ultimate methane potential was significantly reduced (p = 0.04), indicating that the methane production rate was increased. At ISR 0.5, the increase of process stability was also significant with 25% biochar addition, while the control (0%) and 10% biochar addition exhibited high variance among replicates. However, biochar did not affect AD processes under normal substrate loading (ISR 2) and mild substrate overload (ISR 1). Thus, a positive effect of biochar on the AD process was only observed under severe conditions with the highest biochar dosage. Future works should consider optimising substrate loadings and biochar dosages under real conditions when testing the practical application of biochar addition in AD processes.